(untitled) (Journal of Engineering, 2007)
The aim of this study is estimating the critical bed depth in adsorption process through a fixed-bed of granular activated carbon at different bed depths of 0.03, 0.05, 0.08and 0.11m at influent furfural concentration in waste water of 0.2 kg/m3, with constant flow rate of (16.66) × 10-5 m3/min and adsorbent particle size (0.5-1.5) mm. the changing of flow rate and furfural influent concentration had been studied to determine their effects on the critical bed depth value by using bed depth- service time method (BDST). Length of unused bed (LUB) and length of equivalent section of bed had been estimated mathematically during process of the adsorption at different bed depths and during changing the flow rate(8.3× 10-5 m3/min) and influent concentration at same bed depth (0.05m).